Reading the Bible across contexts : Luke's gospel, socio-economic marginality, and Latin American biblical hermeneutics - Autero, Esa (Biblical interpretation series,, 2016)
In Reading the Bible Across Contexts Esa Autero offers a fresh perspective on Luke's poverty texts. In addition to an historical reading, he conducted an empirical investigation of two Latin American Bible reading groups - one poor and the other affluent - to shed light on Luke's poverty texts. The interaction between historical reading and present-day readings demonstrates the impact of socio-economic status on biblical hermeneutics and sheds new light on Luke's views on wealth and poverty. At the same time Esa Autero critically examines liberation theologian's claim that poor are privileged biblical interpreters.